The Effect of Key Financial Indicators on Bank Profitability - Mulyani, Rita; Oktaviani, Retno Fuji; Fauziyah, Nurul Khansa (Shafin: Sharia Finance and Accounting Journal, 2025)
Banking companies experienced fluctuations in average profitability during the 2019-2023 period. This study aims to analyze the effects of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR) and Firm Size on profitability. The research employs a quantitative method using secondary data collected from the Indonesia Stock Exchange and Bank Indonesia websites. The population of the study includes banking sub-sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. The sample was selected using a purposive sampling technique, resulting in 20 companies as the sample. Hypothesis testing was conducted using multiple linear regression analysis with the assistance of the Statistical Package for the Social Sciences (SPSS) software. The findings reveal that the Capital Adequacy Ratio (CAR) and Firm Size (FS) have no effect on profitability, while Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR) significantly influence profitability.